Immunomodulation induced through ornithine decarboxylase DNA immunization in Balb/c mice infected with Leishmania donovani. (May 2018) - Kumar, Akhilesh; Dikhit, Manas Ranjan; Amit, Ajay; Zaidi, Amir; Pandey, Raj Kishor; Singh, Ashish kumar; Suman, Shashi S.; Ali, Vahab; Das, Vidya Nand Rabi; Pandey, Krishna; kumar, Vikas; Singh, Shubhankar Kumar; et al.
Graphical abstract: Highlights: We report on Ld -ODC gene used as a DNA vaccine against VL in a murine model. Protection was conferred mainly by various Th1 cytokines. Vaccine modulated STAT-1 and p38 MAPKinase signaling pathways. ODC vaccination made an impact on parasite killing in spleen after infection. Abstract: We report here a Leishmania donovani ornithine decarboxylase ( Ld -ODC) gene used as a DNA vaccine against visceral leishmaniasis in a murine Balb/c mouse model. This study also evaluated the possible mechanism of action directed by this candidate. We found a Th1 immune response after immunization using an Ld -ODC DNA vaccine, with results based on the rearrangement of TCR-V-α-2, proliferation of Carboxy fluorescein Succinimidyle ester positive T cells, which were able to produce cytokines such as TNF-α, IFN-γ, IL-12 and IL-2, but not IL-4, IL-5, IL-6 and IL-10, and modulations of the STAT-1 and p38 MAP kinase signaling pathways. The results were corroborated with the reduction in the amastigote proliferation and parasite killing in spleens after infection in vitro . We conclude this study suggesting that the Ld -ODC DNA construct could be a new vaccine candidate against visceral leishmaniasis.